2022
DOI: 10.15388/namc.2022.27.26558
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid of Bayesian-based global search with Hooke–Jeeves local refinement for multi-objective optimization problems

Abstract: The proposed multi-objective optimization algorithm hybridizes random global search with a local refinement algorithm. The global search algorithm mimics the Bayesian multi-objective optimization algorithm. The site of current computation of the objective functions by the proposed algorithm is selected by randomized simulation of the bi-objective selection by the Bayesian-based algorithm. The advantage of the new algorithm is that it avoids the inner complexity of Bayesian algorithms. A version of the Hooke–Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is observed that Hooke-Jeeves method is essentially a direct numerical optimization method, which has been reliably and extensively implemented in many industrial problems such as these [11][12][13][14][15][16][17]19]. Due to the fact that numerical data are available from the numerical solutions of a highly non-linear differential equation, minimization of the errors defined previously requires the use of a commensurate method.…”
Section: Modified Hooke-jeeves Optimization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that Hooke-Jeeves method is essentially a direct numerical optimization method, which has been reliably and extensively implemented in many industrial problems such as these [11][12][13][14][15][16][17]19]. Due to the fact that numerical data are available from the numerical solutions of a highly non-linear differential equation, minimization of the errors defined previously requires the use of a commensurate method.…”
Section: Modified Hooke-jeeves Optimization Methodsmentioning
confidence: 99%
“…For instance, Li and Rahman [14] suggested a modification to Hooke-Jeeves optimization method by applying pattern move immediately after a successful pattern move instead of an exploratory move first to maintain the movement in the optimum direction. Litvinas [15] utilized a hybrid optimization of Bayesian-based global search supported with Hooke-Jeeves local search for multi-objective optimization. In that study, the multi-objective problem was reduced to a single objective problem during the application of Hooke-Jeeves method for local refinement process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is difficult to achieve global optimization by using a traditional single optimization algorithm. The PSO-HJ hybrid optimization algorithm, which combines the particle swarm optimization algorithm (PSO) and the Hooke-Jeeves algorithm, firstly provides a set of better initial points through the global search ability of the PSO [27], and then further optimizes the system near the initial points found by the PSO through the local search ability of Hooke-Jeeves [28], thereby enhancing the global search and convergence ability and avoiding premature convergence of the optimization.…”
Section: Optimization Algorithmmentioning
confidence: 99%